2021
DOI: 10.1016/j.ijso.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inhalation aromatherapy of geranium on pain and physiological indices after appendectomy: A double-blind randomized clinical trial

Abstract: Introduction: The aim of the present study was to evaluate the effect of inhalation aromatherapy with sweet-scented geranium essential oil on pain and physiological indices after appendectomy. Methods: This double-blind clinical trial was performed on 120 patients undergoing appendectomy. Aromatherapy was performed with 1% sweet-scented geranium and sweet almond oil in the experimental placebo groups, respectively. Physiological symptoms were recorded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The essential oil of the geranium plant contains geraniol, citronellol, terpineol, and alcohols, which have anticancer, antimicrobial, antiinflammatory, analgesic, and antioxidant effects. 50 Sajjadi et al 28 found a significant pain relief in patients receiving geranium essential oil in comparison with almond oil. The mechanism of pain relief in dysmenorrhea may be related to the analgesic effect of geranium.…”
Section: Discussionmentioning
confidence: 98%
“…The essential oil of the geranium plant contains geraniol, citronellol, terpineol, and alcohols, which have anticancer, antimicrobial, antiinflammatory, analgesic, and antioxidant effects. 50 Sajjadi et al 28 found a significant pain relief in patients receiving geranium essential oil in comparison with almond oil. The mechanism of pain relief in dysmenorrhea may be related to the analgesic effect of geranium.…”
Section: Discussionmentioning
confidence: 98%
“…A three-arm trial by Gazerani et al 114 compared the effect of aromatherapy with geranium and almond oil to no intervention, showing a clinically reduced pain intensity in both groups receiving aromatherapy. No adequate baseline analgesia was reported.…”
Section: Regional Analgesia Techniquesmentioning
confidence: 99%
“…Aromatherapy is the use of essential oils for therapeutic purposes, and it has received attention as an alternative medicine method to control anxiety during medical settings [ 9 ]. It entails inhaling, absorbing, or ingesting essential oils to alleviate anxiety [ 10 ]. The sense of smell can induce chemical changes in the human body that range from pleasant to repulsive.…”
Section: Introductionmentioning
confidence: 99%